FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN INFEKSI SALURAN PERNAFASAN AKUT (ISPA) PADA ANAK BALITA DI PUSKESMAS PANYABUNGANJAE KABUPATENMANDAILING NATAL TAHUN 2014 - lenni marlina silalahi; Sori Muda Sarumpaet; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACT Acute Respiratory Infection (ARI) is acute infection on upper and lower part of respiratory tract caused by virus,fungus and bacteria. Based on data of World Health Organization (WHO) in 2005 the proportion of neonate mortality caused by the respiratory infection is 19 – 25 %. The objective of this research is to study factor related to incidence of ARI on baby or neonate at the area Health Center of Panyabungan Jae Mandailing Natal Regency in 2014. This research is observational study using cross sectional approach. The sample of this research is purposive sampling for 100 person. The data was analyzed by descrivtive study and tested by Chi Square test with 95% CL. The result of research indicates that proportion of patien with ARI is 61 %, the higher on the rage of age group ≥ 12 - < 36 month old ( 58), female for 52 %, a good nutrition status for 94 %, status with exclusive breast milk 39 %, status of complete immunization for 71 %. The result of statistic analysis indicates that is a significant correlation between immunization status (p=0,001, RP;1,819; 95% CL 1,393-2,734),, ventilation (p=0,003, RP;1,633 95% CL 1,256-2,123), occupation density (p<0,001, RP; 2,124; 95% CL 1,461-3,087), burnt anti-mosquito (p<0,001, RP; 1,976; 95% CL 1,545-2,529), and smoking (p<0,001,RP; 2,339; 95%CL 1,743-3,138) with incident of ARI. It is suggested to the health staff to increase the knowledge of society about the importance of immunization and of health house. Keywords: ARI, Immunization status, Ventilation, Occupation density, BurntAnti- musquito, Smoker